Numerical Study the Effect of Blade Number on Archimedes Screw Turbine Utilized in Pico-Hydro in Horizontal Position - anggara, fajar (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2021)
Application of Archimedes Screw Turbine (AST) on pico-hydro has been very popular due to its capability to has a high torque with small flow rate and environmentally friendly to biotic of vicinity. This study uses CFD to investigate AST performance when the number of blades is varied. Independency of mesh is conducted to find an efficient number of mesh and it is obtained at 80 thousand mesh. Variation A, B and C respectively has 4,6, and 9 blades varied to analyze the correspondence with torque, pressure loss and velocity contour. The results show that with a higher number of blades would make higher torque. This is because energy extraction from water would be more efficient at higher number blade. However, the side back at such number would arise such as the higher-pressure loss. This is corresponding to energy balance where a high delta pressure is proportional with a generated energy turbine.